Top Ten Papers - Meeting of the Society of Vascular Surgery SVS2012 - Kyriacou, Efthyvoulos C. (My University, 2026)
Had been selected as one of the Top Ten abstracts of the meeting. This is To promote findings, with a press release distributed to national media.
Keywords: Education